Surgical innovation revisited: A historical narrative of the minimally invasive "Agarwal sliding‐clip renorrhaphy" technique for partial nephrectomy and its application to an Australian cohort. Issue 3 (12th March 2021) - Silagy, A. W.; Young, R.; Kelly, B. D.; Reeves, F.; Furrer, M.; Costello, A. J.; Challacombe, B. J.; Corcoran, N. M.; Kearsley, J.; Dundee, P.; Agarwal, D. K.
Abstract: Objective: To evaluate local clinical outcomes of sliding clip renorrhaphy, from inception to current utilization for open, laparoscopic, and robotically assisted partial nephrectomy. Methods: We reviewed prospectively maintained databases of three surgeons performing partial nephrectomies with the sliding‐clip technique at teaching hospitals between 2005 and 2019. Baseline characteristics, operative parameters, including surgical approach, RENAL Nephrometry Score, and post‐operative outcomes, including Clavien‐Dindo classification of complications, were recorded for 76 consecutive cases. We compared perioperative and 90‐day events with patient and tumor characteristics, stratified by operative approach and case complexity, using Wilcoxon rank‐sum test for continuous variables and the Chi‐squared or Fisher's exact test, for binary and categorical variables, respectively. Results: Open surgery (n = 15) reduced ischemia time and operative time, but increased hospital admission time. Pre‐ and post‐operative estimated glomerular filtration rates did not change significantly by operative approach. Older patients ( P = .007) and open surgery ( P = .003) were associated with a higher rate of complications (any‐grade). Six grade ≥3 complications occurred: these were associated with higher RENAL Nephrometry Score ( P = .016) and higher pathological tumor stage ( P = .045). Limits include smaller case volumes which incorporate the learning curve cases; therefore, these data are most applicable to lower volume teaching hospitals. Conclusion: The sliding‐clip technique for partial nephrectomy was first described by Agarwal et al and has low complication rates, acceptable operative time, and preserves renal function across open and minimally invasive surgeries. This series encompasses the initial learning curve with developing the technique through to present‐day emergence as a routine standard of practice.